Iron oxide nanoparticles alleviate salt-alkaline stress and improve growth by modulating antioxidant defense system in cherry tomato - Raheel Shahzad; Putri Widyanti Harlina; Shahid Ullah Khan; Sri Koerniati; Bernadetta Rina Hastilestari; Ratih Asmana Ningrum; Rizwan Wahab; Ivica Djalovic; P. V. Vara Prasad (Journal of Plant Interactions)
The integration of nanoparticles (NPs) into agriculture is altering traditional methods, enhancing productivity and sustainability. This study explores the application of iron oxide nanoparticles (FeONPs) to mitigate salt-alkaline stress in cherry tomatoes. We investigated FeONPs at three concentrations (FeONP25, FeONP50, FeONP100 mg/kg soil) in pot experiments under non-stress (NS) and salt-alkaline stress (SAS) conditions. SAS conditions decreased biomass and nutrients in untreated plants, a trend reversed by FeONPs. FeONPs treatments significantly boosted pigment levels under SAS, thereby increasing chlorophyll a (10.65–43.05%), chlorophyll b (7.19–41.33%), total chlorophyll (9.84–42.49%), and carotenoids (8.97–36.09%) compared to the control. FeONPs also reduced NPQ under stress, indicating enhanced photosynthetic efficiency. Oxidative stress markers (H2O2, O₂−, and MDA) were strongly induced in control plants but significantly declined with FeONPs treatments. Antioxidants and osmoregulatory substances significantly improved with FeONPs, thereby demonstrating their potential to alleviate SAS in cherry tomato plants.